Study Of Living Al-Qur’an Analysis: Tale Jei Tradition For Hajj Jama'ah In Koto Petai Kerinci Indonesia - Amzaludin Amzaludin; Ahmad Rozy Ride; Aini Mutmainnah (مجلة النور الدولية للقرآن والحديث, 2023)
The study of the living Al-Qur’an tradition of Tale Jei in Koto Petai village uses qualitative-descriptive research methods by describing the facts of the reality of the data that is there for the data collection method, namely by interview and documentation methods to analyze the data obtained from various sources and then describe the results of the analysis. Tale Jei in Kerinci is a legacy of the cultural traditions of ninik mamak or previous scholars, especially in the village of Koto Petai, routinely holding this traditional event before releasing the pilgrims, which in the process contains all about the events of Hajj starting from the pillars of Hajj, Hajj obligations, Hajj requirements, Hajj prohibitions made and sung in the form of songs (Tale). With the help of the living Al-Qur’an, the author will analyze Karl Mannheim's Sociology of Knowledge theory, which focuses on three main points: objective, expressive, and documentary. From the results of the analysis, the author found the verses contained in this tradition by using the Living Al-Qur’an Study of the Tale Jei tradition in Koto Petai village, including 1) Surah al-Mujādalah (58: 11), 2) Surah Āli Imrān (3:97), 3) Surah al-Nahl (16:97), 4) Surah Fāṭir (35:29), and then reveal the spirit of the implementation of the tradition.